PERANCANGAN WEBCOMIC MENGATASI KECANDUAN GAME ONLINE - Ricky Leon Nanda; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Nowadays, teenagers in Indonesia are busy following the trend, namely playing online games. This can be seen from the habit of playing gadgets every day. Besides that, the development of online games is now being rapidly developed in the world, including Indonesia. Without realizing it, teenagers have spent a lot of time trying, until they finally become addicted to Online Games. Online Games can also have a negative effect on players if done excessively. One of the main factors is the intensity of playing online games for teenagers, who can be categorized as addicts if they play 3 hours a day or 20 hours a week. By playing online games excessively, of course it can interfere with learning activities, social activities to the health of adolescents themselves.Based on these problems the Webcomic “Level Up!” design was made. Webcomic media was choosen as the main media because Webcomic can easily reach young people who are familiar with gadgets, so that teens can receive information and messages delivered by Webcomic well, effectively and pleasantly, and Webcomic can be an interesting reading and a first step to reduce teenagers in playing excessive online gaming.In deigning the comic, writer used 4D (Definition, Design, Develop, Disseminate) and 5W+1H (What, Where, Who, Why, How) methods. Author analyzes the “Level Up!” Webcomic that has never been made before. As a study in designing Webcomic and supported by supporting media in the form of Flash Applications, Posters, T=Shirts, Sticker Lines, Pins, Mobile Casing, Key Chains, and Website Add Banners that are able to Promote “Level Up!” Webcomic.Keywords : Addicted Online Games, Level Up, Webcomic